Pelatihan pembuatan media kreatif bagi guru sekolah dasar mitra PGSD UNM Kabupaten Bone - Satriani Satriani; Sudarto Sudarto; Abu Darwis (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Problems faced by students and teachers are the limited understanding of teachers about the importance of using learning media, the tendency to use simple and static learning media, the limited teacher’s undesrstanding in designing and developing creative media, and the lack of training in developing creative and innovative media. While learning media is a tool or intermediary that aims to facilitate the teaching and learning process, in order to make communication effective between teachers and students. This helps the teacher in teaching and makes it easy for students to accept and understand the lesson. The method of implementation carried out in this activity is the lecture method, the method of discussion and question and answer, the method of practice and assignment. The result of the activity was the increase in the ability of PGSD Bone partner elementary school teachers to create effective creative media and in accordance with the learning material to be taught